Evaluation Of The Implementation Of Electronic Medical Records Using The Hot-fit Method In A Public Health Center In East Surabaya - Saadah, Alfina Aisatus; Wahyuni, Titin; Faida, Eka Wilda; Sutha, Diah Wijayanti; Masyfufah, Lilis (Indonesian Journal Publisher, 2025)
The rapid development of information technology that has spread to various sectors of life including health can result in the development of a computer-based medical record system. Computer-based medical records or better known as EMR (Electronic Medical Record) have been used in various hospitals in the world as a complement or replacement for paper-based health records so that they can facilitate the process of managing, accessing, and distributing data or information. Based on the results of brief interviews with health workers working in health centers, it turns out that medical records for obstetric cases are still hybrid. The purpose of this study was to implement the application of Electronic Medical Records using the Hot-Fit method in East Surabaya Health Centers Indonesia. The research method used is descriptive research using a questionnaire sheet as a research instrument. The results of the study obtained data that the application of Electronic Medical Records in East Surabaya Health Centers from system quality, information quality, service quality, system use, organizational structure, facility conditions, and net benefits were categorized as good while for user satisfaction it was suggested to be satisfied and support was suggested to be supportive. So it can be concluded that the application of EMR was given well. Suggestions for the Health Center are the need to improve the system and network, the need to complete the information in the EMR in detail, the need to provide training to health workers in the use of EMR, and the need for socialization by superiors regarding the policy on the use of EMR.